Biomass Production in Two Tropical Herbaceous Legumes as Influenced by the Structural Characteristics of Mine Spoil - Singh, Arvind (Indian Forester, 2007)
The effect of structural characteristics of mine spoil was studied on biomass production of two tropical herbaceous legumes Stylosanthes hamata and Stylosanthes humilis. The structural variation had marked influence on biomass production. The root, shoot and total biomass production was greater at less rocky spoil site than more rocky spoil site in both the leguminous species. However, the root/shoot ratio was greater at more rocky spoil site than less rocky spoil site in both the species.